2017
DOI: 10.2337/dc17-0738
|View full text |Cite
|
Sign up to set email alerts
|

Increased Liver Fatty Acid Uptake Is Partly Reversed and Liver Fat Content Normalized After Bariatric Surgery

Abstract: The findings suggest that in a postoperative state, intrahepatic fatty acids are not stored in the liver but are used for oxidation to provide energy. Changes in perfusion may contribute to improved liver metabolism postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Abdominal adipose tissue, 14 pancreas 16 and liver 17 NEFA uptake rates concerning the same study patients have been published previously.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Abdominal adipose tissue, 14 pancreas 16 and liver 17 NEFA uptake rates concerning the same study patients have been published previously.…”
Section: Introductionmentioning
confidence: 97%
“…For this study, we aimed to assess the effects of bariatric surgery on NEFA uptake, on triglyceride content and on the proportion of brown fat in the supraclavicular fat depot of morbidly obese patients. Abdominal adipose tissue, pancreas and liver NEFA uptake rates concerning the same study patients have been published previously.…”
Section: Introductionmentioning
confidence: 98%
“…Although often suggested to be the major contributor to liver TAG, Donnelly et al (8) using stable-isotope tracer methodology, reported that plasma NEFA contributed between 45 and 74 % to liver TAG (after a 4 d stable-isotope labelling procedure); thus it is plausible that some, but not all, individuals develop NAFLD due to an increased fatty acid flux from adipose tissue to the liver. Positron emission tomography/computed tomography in combination with labelled palmitate ( 11 C) or a palmitate analogue fluoro-6-thia-heptadecanoic acid have been used to assess hepatic fatty acid uptake (17,18) . It was found that hepatic fatty acid uptake was higher, although not significantly different, in obese compared with overweight control subjects (17) whilst in morbidly obese individuals hepatic fatty acid uptake is significantly higher before and 6 months after bariatric surgery than in lean controls, despite liver fat content being normalised (18) .…”
Section: Fatty Acid Sources: Adipose Tissuementioning
confidence: 99%
“…In a recent study in morbidly obese subjects, Immonen and coworkers, using a palmitate analog, [ 18 F]-fluoro-6-thiaheptadecanoic acid ( 18 F-FTHA), found morbidly obese subjects to have elevated hepatic fatty acid uptake (HFU) before bariatric surgery that decreased after surgery, though it did not normalize relative to lean subjects. Intriguingly, HFU and liver fat content in these patients were not related[ 78 ]. Iozzo et al[ 79 ] using 11 C-palmitate-PET scanning showed that obese subjects have higher rate of fatty acid oxidation than lean subjects.…”
Section: Pet To Study Liver Metabolismmentioning
confidence: 99%
“…According to these authors, the assessment of fatty acid oxidation is of major importance in characterizing subjects with NAFLD, since fatty acid oxidation is a significant source of reactive oxygen species in obesity-related hepatic lipotoxicity. Finally, with appropriate modeling, PET like MRI can be used in the quantification of liver perfusion in humans[ 78 , 80 ].…”
Section: Pet To Study Liver Metabolismmentioning
confidence: 99%